Ejercicio y sensación de posición articular en la rodilla. Efecto agudo del ejercicio de calentamiento y del ejercicio intenso, en acciones musculares concéntricas y excéntricas. - Duilio Carughi Bonelli (2017)
Objective: To describe the acute effect of a warm-up routine normally used in sports that have some contact with the floor, as well as to observe and compare the sensation of the articular position of the knee of the dominant member after exposure to fatigue stimuli, either in eccentric or concentric contraction to compare its acute effect.Design: Descriptive, comparison of repeated and independent measuresParticipants: 20 subjects with a mean age of 19.5 ± 1.2, who performed sport with a minimum of weekly volume in interval of at least 180 to 270 minutes distributed 3 times per week, which were separated into two groups, concentric group (n=10), eccentric group (n=10)Measurements: Evaluation of the joint position sense (JPS) of the knee, passively, through an isokinetic dynamometer, in three different moments: rest, after a warm up and following a fatigue stimulus for the quadriceps, in either concentric or eccentric.Results: Absolute Angular Error (AAE) mean values of 40° and 60° decreased from resting condition to post-warm-up condition, but with only statistically significant (p <0.05) for the 40° target position (8.5 ± 4.4 vs. 6.1 ± 4.2). For the means in the comparison of the acute effect between the warm-up and the fatigue stimulus did not show statistically significant differences, for the comparison of the two modes of contraction used (concentric vs eccentric), there were no statistically significant differences (p ˃ 0.05).Conclusions: The warm-up exercise improves the JPS. The concentric and eccentric exercise protocols were not intense enough to induce neuromuscular fatigue with a repercussion in the increase of AAE as an indicator of JPS.